THE The Influence Of School Organizational Climate And Work Motivation On The Professional Competence Of Elementary School Teachers - Dewi, Endah Kurnia Sinta; Yuliejantiningsih, Yovitha; Haryati, Titik (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study examines school organizational climate and work motivation effects on elementary teachers' professional competence in Jambu Subdistrict, Semarang Regency's 18 rural schools. Previous studies found moderate correlations (Dharmawaty et al., 2022: r = 0.45; Sumantri & Whardani, 2017: R² = 0.28), but simultaneous examination in rural contexts remains limited. Using ex post facto design, 125 teachers were surveyed through proportional random sampling. Instruments measured professional competence (content mastery, student understanding, curriculum application), organizational climate (learning quality, inclusivity, learning culture), and work motivation (internal/external factors) with validated items like "I understand subject scientific structure" and "School promotes innovative strategies." Results showed significant positive effects: organizational climate (r = 0.634, R² = 0.402) and work motivation (r = 0.630, R² = 0.397) individually, with combined influence of 56.2%. These large effect sizes indicate substantial practical significance for real educational settings. Dimensional analysis revealed learning content knowledge (0.333) and learning culture (0.380) had lowest contributions, while internal-external motivation contributed equally (0.634). Findings align with Herzberg's Motivation-Hygiene Theory and Organizational Climate Theory, confirming that both intrinsic satisfaction and environmental factors shape professional performance. The study recommends prioritizing teacher subject mastery through continuous training and strengthening organizational learning culture via structured professional development.